STRATEGI KOMUNIKASI PUBLIK DINAS KESEHATAN KOTA DEPOK DALAM UPAYA PENANGANAN COVID-19 - Laras Sari Jadra (2023)
The background of this study is the need for information on the public communication strategy of the Depok Public Health Department to manage the spread of the Covid-19 virus in the Depok city. Purpose of this study the researchers wanted to understand how clear and comprehensive the public communication strategy implemented by the Depok Health Department was. This study used the SMCR communication model, which assumes that health facilities have a strategy for providing information. The research paradigm used is constructivism with a qualitative research approach and a case study approach. Data collection took the form of in-depth interviews with five employees of Depok's Health Department. The end result of this research is that the community collaborates and communicates directly with various parties including community leaders, supported by different industries in addition to using online media as an information medium. Obstacles faced by the health department were inaccurate information disseminated to the city government, deficient data retrieval systems, and understaffing in the DePauw Health Department's official media management unit.